Penerapan E-System Terhadap Kepatuhan Wajib Pajak UMKM Di Wilayah KPP Pratama Gianyar - Cokorda Krisna Yudha; Cok Istri Ratna Sari Dewi (ARTHA SATYA DHARMA, 2022)
The Covid-19 virus pandemic has had a very big impact on various aspects of life to aspects of economic stability both domestically and abroad. Information technology is required to develop for various sectors due to restrictions due to the Covid-19 Pandemic. The Directorate General of Taxes also developed its technology to reduce the impact of the spread of the virus, so that all taxpayers do not need to go to the tax office to report their tax period and yearly. The online service can be accessed on the www.djp.go.id page. The population in this study is MSMEs registered with the KPP Pratama Gianyar Regency, the sample determination uses the slovin formula in determining the number, which is 100 MSMEs. The analysis method used in this study is a multiple linear regression test. The results of this study accept the hypothesis that the E-System has a positive effect on the compliance of MSME taxpayers. The advice that can be given for further research is to conduct research on MSME Taxpayers in other regions, as well as add other factors that can affect taxpayer compliance in Indonesia.